SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU DI SMA NEGERI 1 NGABANG - Tony Akbar; Wahyudi Wahyudi; Usman Radiana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractNew student admission with zoning is the process of accepting new students with predetermined qualifications using the residential zone from school to house. This study aims to determine the process of registration and acceptance of PPDB with the zoning system in SMA Negeri 1 Ngabang. This research uses a qualitative approach and type of case study research. The subjects in this study were the principal, the vice principal for student affairs, and the head of the PPDB committee. Data collection procedures, namely observation, interviews and documentation. The findings from the results of this study are: (1) Student recruitment with a zoning system is a PPDB system that is seen based on the distance between the prospective students' residence and the school, not based on the UN score. (2) Selection is a process carried out to recruit students according to the rules to be accepted in school. (3) Placement is a follow-up to the results of the selection process to be accepted into a school and does not have specific criteria for placement. (4) Evaluation is an assessment process so that the PPDB acceptance process in the future can run better. (5) PPDB constraints can cause the PPDB acceptance process to not be carried out properly. The conclusions from the research results are: Acceptance of the PPDB zoning system using zones makes it easier for parents to register their children because of the close distance between school and home. Can be done online. Keywords: Acceptance of New Students,  Zonation System